Development of Problem-Based Learning Model in Improving Elementary School Students' Knowledge and Attitude of Preparedness in Facing Floods - Ceisilia Mira Sholikhah; Juhadi Juhadi; Ananto Aji; Aprillia Findayani; Eva Banowati (Universitas Lambung Mangkurat, 2025)
This study aims to evaluate the effectiveness of the Problem-Based Learning (PBL) model in improving knowledge and attitudes toward flood preparedness among elementary school students, without comparing it to other teaching methods. The research location is at SD 2 Kesambi, Mejobo Subdistrict, Kudus Regency, Central Java. The method used in this research is Pre-experimental Design with a quantitative approach. The design in this study is One-Group Pretest-Posttest Design. The design in this study used one group of subjects by giving an initial test, treatment with the Problem-Based Learning (PBL) model , and a final test. The research population consists of all 154 students at SD 2 Kesambi, with the sample comprising third-grade students (28 students) and fifth-grade students (24 students) selected using stratified random sampling. Data collection was conducted through attitude questionnaires, knowledge tests (pretest and posttest), observations, interviews, documentation, and literature reviews. Data analysis utilized descriptive statistics, paired sample t-tests, and N-Gain tests. The results showed a significant increase in students' knowledge: the average pretest and posttest scores for third grade increased from 49.21 to 87.57 (N-Gain = 0.75, high category), while fifth grade increased from 54.25 to 85.75 (N-Gain = 0.68, moderate category). The paired sample t-test yielded a significance value of < 0.001, indicating a significant difference. An increase in preparedness attitudes was also evident from the dominance of student responses in the “agree” category (Grade III: 89.28%; Grade V: 83.3%). Thus, the Problem-Based Learning (PBL) model has proven effective in enhancing students' preparedness for flood disasters